2011
DOI: 10.1177/1938965510389297
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in Tipping: Testing the Role of Norm Familiarity

Abstract: On average, blacks tip less than whites in the United States. As a result, many servers dislike waiting on black tables and deliver inferior service to those blacks seated in their sections. Furthermore, this race difference makes it difficult to attract and retain waitstaff in predominately black neighborhoods, which makes such neighborhoods less attractive places for corporations to locate full-service restaurants. To address these issues, race differences in tipping need to be sizably reduced, which require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 9 publications
4
36
0
1
Order By: Relevance
“…Also supporting the influence of perceived expectations, consumers' tip sizes in U.S. restaurants are strongly related to their perceptions of the amounts people are expected to tip and consumers' frequencies of tipping a variety of other service providers (e.g., bartenders, hair cutters, parking valets, pizza delivery drivers, and taxicab drivers) are strongly related to their perceptions that such tips are normative and expected (Lynn, 2011). People could comply with social expectations because they have internalized those expectations and the internalization of the restaurant tipping norm could be more likely among frequent restaurant diners and affluent consumers, so the effects of perceived tipping norms and of bill size and its interactions with patronage frequency and restaurant expensiveness need not reflect tippers' efforts to gain or keep social esteem, but they are consistent with such motives and efforts.…”
Section: Gain or Keep Social Esteemmentioning
confidence: 91%
“…Also supporting the influence of perceived expectations, consumers' tip sizes in U.S. restaurants are strongly related to their perceptions of the amounts people are expected to tip and consumers' frequencies of tipping a variety of other service providers (e.g., bartenders, hair cutters, parking valets, pizza delivery drivers, and taxicab drivers) are strongly related to their perceptions that such tips are normative and expected (Lynn, 2011). People could comply with social expectations because they have internalized those expectations and the internalization of the restaurant tipping norm could be more likely among frequent restaurant diners and affluent consumers, so the effects of perceived tipping norms and of bill size and its interactions with patronage frequency and restaurant expensiveness need not reflect tippers' efforts to gain or keep social esteem, but they are consistent with such motives and efforts.…”
Section: Gain or Keep Social Esteemmentioning
confidence: 91%
“…Researchers have been able to rule out the impact of socio-economic and discrimination of service quality on the difference in tipping habits (Lynn, 2006). Furthermore, it has been shown that difference in tipping habits can be attributed to a lack of understanding of social norms (Lynn, 2011).…”
Section: Found That Africanmentioning
confidence: 99%
“…Thus, restaurant servers and their managers can expect below average tips from Black customers regardless of their social class. Furthermore, advocates of campaigns to educate Blacks about the restaurant tipping norm as a means of reducing black-white differences in tipping behavior (see Amer, 2002;Lynn, 2011;Wallace, 2008) probably need to include upper-class Blacks in the target market for those campaigns.…”
Section: Discussionmentioning
confidence: 98%
“…For example, previous research has found that Blacks in the United States tip less than Whites in large part because they have different perceptions and beliefs about the customary or normative tip amount (Lynn, 2004(Lynn, , 2006b(Lynn, , 2011. In fact, approximately 70 percent of White adults in the U.S. believe that it is customary or normative to tip 15-20 percent of the bill size in restaurants while only about 35 percent of Black adults in the U.S. hold this belief (Lynn, 2004(Lynn, , 2006b.…”
mentioning
confidence: 96%